How Students’ Motivation and Learning Experience Affect Their Service-Learning Outcomes: A Structural Equation Modeling Analysis - Lo, Kenneth W. K.; Ngai, Grace; Chan, Stephen C. F.; Kwan, Kam-por (Frontiers in Psychology, 2022)
Guided by the expectancy-value theory of motivation in learning, we explored the causal relationship between students’ learning experiences, motivation, and cognitive learning outcome in academic service-learning. Based on a sample of 2,056 college students from a university in Hong Kong, the findings affirm that learning experiences and motivation are key factors determining cognitive learning outcome, affording a better understanding of student learning behaviour and the impact in service-learning. This research provides an insight into the impact of motivation and learning experiences on students’ cognitive learning outcome while engaging in academic service-learning. This not only can discover the intermediate factors of the learning process but also provides insights to educators on how to enhance their teaching pedagogy.